Exposure of Belt and Road Economies to China Trade Shocks - Bastos, Paulo (World Bank, Washington, DC, 2018)
The Belt and Road Initiative seeks to deepen China's international integration by improving infrastructure and strengthening trade and investment linkages with countries along the old Silk Road, thereby linking it to Europe. This paper uses detailed bilateral trade data for 1995-2015 to assess the degree of exposure of Belt and Road economies to China trade shocks. The econometric results reveal that China's trade growth significantly affected the exports of Belt and Road economies. Between 1995 and 2015, the magnitude of China's demand shocks was larger than that of its competition shocks. However, competition shocks became more important in recent years, and were highly heterogeneous across countries and industries. Building on these findings, the paper documents the current degree of exposure of Belt and Road economies to China trade shocks, and discusses policy options to deal with trade-induced adjustment costs.